2005
DOI: 10.1016/j.cmet.2005.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The HNF-1 target Collectrin controls insulin exocytosis by SNARE complex formation

Abstract: Defective glucose-stimulated insulin secretion is the main cause of hyperglycemia in type 2 diabetes mellitus. Mutations in HNF-1alpha cause a monogenic form of type 2 diabetes, maturity-onset diabetes of the young (MODY), characterized by impaired insulin secretion. Here we report that collectrin, a recently cloned kidney-specific gene of unknown function, is a target of HNF-1alpha in pancreatic beta cells. Expression of collectrin was decreased in the islets of HNF-1alpha (-/-) mice, but was increased in obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 41 publications
7
140
0
1
Order By: Relevance
“…This is consistent with the observed role of glutamine in the release of insulin from pancreatic ␤-cells (38). We could detect B 0 AT1 mRNA in pancreas but do not know whether it is expressed in ␤-cells, where the B 0 AT1 trafficking subunit collectrin has been found (39,40). It has been reported that some strains of C57Bl/6J mice have deletions in the nicotinamide nucleotide transhydrogenase (Nnt), resulting in a reduced insulin response (17).…”
Section: Discussionsupporting
confidence: 73%
“…This is consistent with the observed role of glutamine in the release of insulin from pancreatic ␤-cells (38). We could detect B 0 AT1 mRNA in pancreas but do not know whether it is expressed in ␤-cells, where the B 0 AT1 trafficking subunit collectrin has been found (39,40). It has been reported that some strains of C57Bl/6J mice have deletions in the nicotinamide nucleotide transhydrogenase (Nnt), resulting in a reduced insulin response (17).…”
Section: Discussionsupporting
confidence: 73%
“…LCM was performed as previously described [30]. Frozen pancreatic Quantitative measurements of specific transcripts were acquired by real-time RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The C-terminal domain of Tmem27 appears to be involved implication in glucose-stimulated insulin exocytosis and and/or ß-cell mass in pancreas, 67,68 as well as renal collecting duct primary cilium formation and polycystic kidney disease. 70 As described more in detail in later paragraphs, Tmem27 has also been shown to be critical for the correct expression of amino acid transporters in kidney.…”
Section: 11mentioning
confidence: 99%
“…65 Tmem27 has been shown to be expressed in liver, lung, endocrine pancreas and kidney proximal tubule brush border membrane and collecting duct, hence the misleading name Collectrin. 12,13,67,68 Given the lack of Tmem27 catalytic activity, it does not seem to play a role in the classical RAS although an implication in the development of salt sensitive hypertension has been suggested. 69 Tmem27 has been shown to bind proteins involved in intracellular and membrane protein trafficking and ciliary movement such as γ-actin-myosin II-A, snapin, SNAP-25 and polycystin-2-polaris complexes.…”
mentioning
confidence: 99%